2021
DOI: 10.1183/23120541.00147-2021
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmia in heart failure patients with reduced ejection fraction and central sleep apnoea

Abstract: Cheyne-Stokes respiration (CSR) may trigger ventricular arrhythmia in patients with heart failure with reduced ejection fraction (HFrEF) and central sleep apnoea (CSA). This study determined the prevalence and predictors of a high nocturnal ventricular arrhythmia burden in patients with HFrEF and CSA (with and without CSR) and to evaluate the temporal association between CSR and the ventricular arrhythmia burden.This cross-sectional ancillary analysis included 239 participants from the SERVE-HF major sub-study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…Therefore we implemented stringent training of the investigators for ECG analysis according to standardized guidelines [18] . Such training of investigators has not been reported in previous studies using single-lead ECGs during PSGs in subjects with HFrEF [23] , [35] , [36] , [37] , [38] .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Therefore we implemented stringent training of the investigators for ECG analysis according to standardized guidelines [18] . Such training of investigators has not been reported in previous studies using single-lead ECGs during PSGs in subjects with HFrEF [23] , [35] , [36] , [37] , [38] .…”
Section: Discussionmentioning
confidence: 91%
“…Employing quality assurance methods is essential in a population with HFrEF, in whom wide QRS complexes and both atrial and ventricular pacing are common [23] , [32] , in order to achieve similar inter-observer agreement on electrocardiographic variables using a single-lead ECG recorded during PSG compared to studies in which participants did not have overt heart disease [33] , [34] . Therefore we implemented stringent training of the investigators for ECG analysis according to standardized guidelines [18] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations